Beneficial health effects of treatment with flotation-REST on stress and blood pressure - Szypłowska, Małgorzata; Kuś, Adrian; Gładysz, Konrad; Neścior, Małgorzata; Szpiech, Kamil (Journal of Education, Health and Sport, 2019)
Flotation-REST is a method where an individual is immersed in a tank filled with water of an extremely high salt concentration, whereby environmental stimulation is restricted. Restricted environmental stimulation technique (REST) is a method used to achieve a deep relaxation and subsequent beneficial health effects on stress and relaxation. The purpose of this paper is to evaluate potential positive health effects of flotation-REST.Flotation-REST treatment decreased the degree of stress. Another study's results indicate that flotation-REST reduces systolic and diastolic blood pressure due to greater relaxation. It was concluded that flotation-REST has beneficial effects on decreasing stress, therefore the method has potential as a complementary treatment of stress-related ailments. However, more studies are warranted to further evaluate the treatments efficacy.